Controller design for PMSG-wind turbine - Pua, Yong Xiang. (2010)
Permanent magnet synchronous generator (PMSG) direct driven wind turbines are getting more popular as the cost of the materials required for the permanent magnet had decreased over the years. Hence, it is important that the appropriate controller system is designed to ensure the stability of the system. This project explores the design of a PMSG wind turbine generation system (WTGS). Conventional control theory is applied to the system such that it is able to achieve maximum efficiency at lower wind speeds while capping the power output at higher wind speeds. The system is subdivided into different blocks and the s-domain representations in the dq0 frame are obtained for each block. With the obtained transfer function, cascaded PI controllers are designed with the pole-zero cancellation method. Two models of the WTGS are setup in Matlab/Simulink. One is made up of the blocks using the available library in SimPowerSystems while the other is the mathematical implementation of the WTGS. The models are then connected to an infinity bus to evaluate the performance of the WTGS. In both models, the designed system is able to maintained high efficiency at low wind speeds and regulates power transmission at higher wind speeds. However, in the SimPowerSystems model, the performance of the inner current loops is not satisfactory due to the nature of the design methodology. As a result, the mathematical model is able to achieve unity power factor most of the time while the SimPowerSystems model is unable to do so. Further improvement is required on the models so that more sophisticated control strategies can be explored.